Upaya Pemerintah Provinsi Riau dalam Menangani Kasus Kebakaran Hutan Riau berdasarkan ASEAN Agreement on Transboundary Haze Pollution - Dian Novita Dewi (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2023)
This research discusses the efforts of the Riau Provincial Government in raising awareness among the local community to prevent forest and land fires, which have become a serious issue in the Southeast Asian region. Grounded in the theories of compliance, neoliberal institutionalism, and the concept of international regimes, this study reveals that Indonesia, as the main actor in the ASEAN Agreement on Transboundary Haze Pollution (AATHP), has made efforts to comply with the agreement. Preventive measures against forest and land fires involve the central and local governments, as well as the active participation of local communities. Education and socialization programs about the dangers of forest and land fires, relevant regulations, and their negative impacts are crucial components of the prevention strategy. Furthermore, private companies such as Asian Agri and PT SRL play a significant role in supporting these prevention programs. The research findings indicate that despite numerous efforts, the issues of forest fires and transboundary air pollution remain serious concerns in the Southeast Asian region. AATHP, as a binding legal framework for Indonesia, requires more extensive and sustainable efforts to achieve the desired goals of preventing transboundary air pollution. Community awareness and cooperation between government, private entities, and NGOs will be key to addressing this issue.